1.55 μm Narrow-Linewidth Pulsed Laser Based on MgO:PPLN - Yaling Yang; Guorui Lv; Lei Guo; Haiping Xu; Hui Kong; Jiaqi Wen; Jintian Bian; Qing Ye; Kejian Yang; Jingliang He (Photonics, 2023)
A high-power narrow-linewidth 1.55 μm pulsed laser, based on MgO:PPLN OPO, has been achieved using a F–P etalon. The pump source is a 1064 nm acousto-optical (AO) Q-switched Nd:YAG laser with a repetition rate of 10 kHz. Under the maximum pump power of 18 W, the signal output power of 2.57 W is demonstrated at 1551.1 nm with a linewidth of 0.07 nm, corresponding to a slope efficiency of 16.1%. Different from traditional inversion lasers, the narrow-linewidth wavelength tunability of approximately 1.55 μm can be realized by changing the temperature.